Virus and host-specific differences in oral human herpesvirus shedding kinetics among Ugandan women and children. Issue 1 (December 2017) - Matrajt, Laura; Gantt, Soren; Mayer, Bryan; Krantz, Elizabeth; Orem, Jackson; Wald, Anna; Corey, Lawrence; Schiffer, Joshua; Casper, Corey
Abstract Human herpesviruses (HHV) establish lifelong latent infection and are transmitted primarily via shedding at mucosal surfaces. Each HHV causes a unique spectrum of disease depending on the infected individual's age and immunity. We collected weekly oral swabs from young children and mothers in 32 Ugandan households for a median of one year. We characterized kinetics of oral shedding during primary and chronic infection for each virus. Cytomegalovirus (CMV), Epstein-Barr virus (EBV), and HHV-6 were shed at high rates following primary infection. The rate of oral herpes simplex virus (HSV) shedding was lower overall, and children and mothers with chronic HSV infection had lower shedding rates than children with primary infection. CMV shedding rate and viral load were higher in children with primary infection compared to children with chronic infection, and even lower in mothers with chronic infection. HHV-6 shedding rate and viral load were similar between children with primary or chronic infection, but lower in mothers. EBV shedding rate and quantity decreased less dramatically in mothers versus children, with HIV-positive mothers shedding at a higher rate than HIV-negative mothers. Each HHV has a distinct pattern of oral shedding which depends partially on the age and immune status of the host.